Peringatan The Economist Terkait Kepemimpinan Vladimir Putin: Analisis Semiotik Sampul Majalah “A Tsar is Born” - Zeremy Giovanni (Unitri Press, 2023)
Texts contained on magazine covers, both visual and typographical, appears through rigid editorial process and is presented with a specific purpose. However, signs on a magazine cover may be interpreted differently, according to the reader’s references. Therefore, this study focuses on interpreting the meaning contained in a magazine cover. Researcher argue that The Economist is trying to warn about the development of President Vladimir Putin’s government, which led to the leadership style before the Russian revolution in 1917. This study was carried out using interpretive paradigm with qualitative descriptive method. Collection of data were obtained from the cover of A Tsar is Born and other related secondary data. The analysis was carried out using the semiotic analysis method of Charles Sanders Peirce by paying attention to the trichotomy of objects, representamen, interpretants. Through observation raised eight signs that will become sources of research analysis, namely clothing illustration, ties, one eye medal, Crimean medal, hammer and sickle medal, shoulder decoration, illustration of Putin’s facial expression, and the typography “100 years after the Russian revolution”. The result of the analysis show that each meaning of the sign on the cover of the magazine leads to The Economist’s concern regarding the development of President Vladimir Putin’s leadership in Russia. This concern become consideration for The Economist to warn about this issue, and describe it through the cover of A Tsar is Born. Abstrak Teks yang terkandung pada sampul majalah, baik visual maupun tipografi, muncul melalui proses editorial yang ketat dan ditampilkan dengan tujuan tertentu. Namun, tanda-tanda yang terdapat pada sampul majalah dapat diinterpretasikan berbeda, sesuai dengan referensi pembaca. Maka dari itu, penelitian ini berfokus pada penginterpretasian makna yang terkandung pada sampul majalah. Peneliti berargumen bahwa majalah The Economist berupaya untuk memberikan peringatan terkait perkembangan kepemimpinan Presiden Vladimir Putin, yang semakin mengarah pada gaya kepemimpinan tsar sebelum revolusi rusia tahun 1917. Penelitian dilaksanakan menggunakan paradigma interpretatif dengan metode kualitatif jenis deskriptif. Data didapatkan melalui sampul majalah edisi A Tsar is Born dan data-data sekunder yang berkaitan. Analisis dilaksanakan menggunakan metode analisis semiotika Charles Sanders Peirce dengan memperhatikan trikotomi objek, representamen, dan interpretan. Hasil observasi memunculkan delapan tanda yang akan menjadi sumber analisis penelitian yaitu ilustrasi pakaian, dasi, medali sebelah mata, medali Krimea, medali palu dan arit, hiasan pundak, ilustrasi ekspresi wajah, dan tipografi “100 years after the Russian revolution”. Hasil analisis menunjukan bahwa setiap makna tanda pada sampul majalah mengarah pada kekhawatiran majalah The Economist terkait perkembangan kepemimpinan Presiden Vladimir Putin di Rusia. Hal tersebut menjadi pertimbangan bagi The Economist untuk membahas isu ini, dan menggambarkannya melalui sampul majalah edisi A Tsar is Born.